دراسة مخبرية لتقييم فعالية تقنية الانزلاق المنحني في إرجاع الأنياب العلوية - تيزيني, محمد; مسيلماني, محمد بشار; معتوق, محمد (Latakia University Journal -Medical Sciences Series, 2019)
مقدمة: يعتبر إرجاع الأنياب مرحلة هامة في العديد من الحالات التقويمية المعالجة بالقلع. هدف البحث: مقارنة المقاومة الاحتكاكية بين تقنية الانزلاق المنحني المطورة و تقنية الانزلاق التقليدية, واختبار فعالية التقنية الجديدة في إرجاع الأنياب العلوية على جهاز التايبودونت. المواد و الطرق: تكونت عينة اختبار الاحتكاك من 20 سلكاً مستقيماً 0.019×0.025-inch فولاذياً لا صدئاً (مجموعة السلك المستقيم), و 20 سلكاً منحنياً 0.019×0.025-inch فولاذياً لا صدئاً تشكل قوساً من دائرة نصف قطرها 4 سم (مجموعة السلك المنحني). و تكونت عينة الاختبار على جهاز التايبودونت من 24 جهازاً لإرجاع الأنياب باستخدام تقنية الانزلاق المنحني قسمت إلى مجموعتين متساويتين, استخدم في المجموعة الأولى الإرساء المطلق و في المجموعة الثانية تم التزليق بشكل اعتيادي. النتائج: مقدار الاحتكاك في مجموعة السلك المنحني أقل مما هو في مجموعة السلك المستقيم, و كان الفرق ذا دلالة إحصائية (P < 0.1). أظهر اختبار التايبودونت في مجموعة الإرساء المطلق حدوث إمالة وحشية بسيطة لجذور الأنياب (-1.44°) مع غرز للأنياب بمقدار 2.07 mm. بينما أظهرت مجموعة التزليق الاعتيادي حركة جسمية للأنياب مع المحافظة على الوضعية العمودية. وحققت كلتا المجموعتين سيطرة تامة على انفتال الأنياب. الاستنتاجات: الحركة الانزلاقية المنحنية (نصف قطر دائرة الحركة 4 سم) أقل احتكاكا من الحركة الانزلاقية المستقيمة عندما يشكل محور القوة المطبقة 10˚ مع مستوى الأنبوب. حققت تقنية الانزلاق المنحني فعالية جيدة في إرجاع الأنياب العلوية. Introduction: Canine retraction is an important stage in many orthodontic cases treated with extraction. Aim of study: Compare the friction between a curved sliding technique and conventional sliding mechanics, and evaluate the efficiency of the new technique in canine retraction on a typodont. Materials and methods: The friction test sample consisted of 20 0.019 × 0.025-inch stainless steel straight archwires (straight archwire group) and 20 0.019×0.025-inch stainless steel archwires which formed an arc of a circle (with a radius of 4 cm) (curved archwire group). The typodont test sample consisted of 24 canine retractors using curved sliding technique. They were divided into two equal groups, absolute anchorage was used in the first group while usual sliding was done in the second group. Results: The friction in (curved archwire group) was less than in (straight archwire group) and the difference was significant (P<0.1). The typodont test showed, in absolute anchorage group, slight distal tipping of canine roots (-1.44˚) and canine intrusion (2.07mm), while usual sliding group showed bodily movement of the canine with maintain of the vertical position. Both groups showed perfect rotational control of the canines. Conclusions: Curved sliding movement (with a radius of movement circle equals 4 cm) was less fricative than straight sliding movement when force axis formed 10˚ with tube level. Curved sliding technique showed a good efficiency in canine retraction.